PENERAPAN BUILDING INFORMATION MODELING (BIM) DALAM MANAJEMEN KONSTRUKSI ALIRAN SUNGAI UNTUK PENGELOLAAN BANJIR STUDI KASUS DAERAH ALIRAN SUNGAI (DAS) KIPP IKN (IBU KOTA NUSANTARA) - Taufan Hary Saputra; Maraden Panjaitan; Eswan, Eswan (LPSDI Bina Patria, 2025)
The implementation of Building Information Modeling (BIM) has become a major trend in the modern construction industry, especially in the Development of the Indonesian Capital City and construction project management. BIM technology enables better integration between all aspects of a project, including planning, design, construction, and facility management. This study aims to examine the impact and benefits of BIM implementation in construction project management and the challenges faced in its implementation. The implementation of BIM provides efficiency in team coordination, reduces design conflicts, and improves project resource management. In addition, BIM enhances collaboration between stakeholders and enables more accurate decision making based on integrated information. However, BIM implementation also faces several challenges such as high initial investment costs, the need for in-depth technical skills, and interoperability issues between different BIM platforms